KAJIAN KELAYAKAN INVESTASI PENGEMBANGAN SPAM DI KOTA MANADO (STUDI KASUS DI KECAMATAN MAPANGET) - Mamudi, Lanny; Mandagi, R J; Lumeno, Shirly (Sam Ratulangi University, 2017)
The change of Spatial Plan of Manado City in district Mapanget from the sub service center of the city into a new city center made the growth of infrastructure increased along with the rapid growth of population causing the increasing of drinking water demand in the area. To meet the needs of drinking water in district Mapanget required a water supply system development by conducting a feasibility study so that with the feasibility result is expected to have an effort from the government and the investors to make water supply system investment in the district of Mapanget.The feasibility study process of water supply system in district Mapanget starts from identifying the factors become an investment feasibility indicator and conducting water supply system development analysis from that indicator. From the analysis of the feasibility factors we perform the economic feasibility calculation of the calculation of Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP).The results of identification obtained by water supply system feasibility factors are technical, social, institutional and economic. From each factor is obtained the following results, for technical factors made water supply system distribution system planning that consists of raw water sources are Kuwil Reservoir, production units in the form of installation of water management and pumps, reservoir units and pipeline units. From the social factor, the water requirement in the year of 2025 is 12,585,91 m3 / day and the year 2036 is 19,741,23 m3 / day with the subsidy level of water supply system from the community as much as 51%. As for the institutional factor, management and operation of water supply system is done by the Provincial Government of North Sulawesi in this case UPTD Air Minum Public Works Department of North Sulawesi Province. The results of the calculation of the investment economy of several assumptions on interest rates obtained value of BCR is more than 1, NPV is positive, IRR value is greater than the value of interest rate used and Payback Period for interest rate 5% - 20% less than 15 years so the project is declared feasible to be implemented.Â Keywords: Investment feasibility, water supply system, BCR, NPV, IRR, Payback PeriodÂ